2005
DOI: 10.1111/j.1365-2109.2005.01294.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of size grading on growth, survival and cheliped injuries of signal crayfish (Pacifastacus leniusculus Dana) summerlings (age 0+)

Abstract: E¡ects of size grading and stocking density on growth and survival of 3.5-month-old signal cray¢sh (Pacifastacus leniusculus Dana) juveniles were investigated in a 3 Â 2 factorial design with size group (small, large and mixed) and stocking density (25 and 200 individuals m À 2 ) as factors for 90 days. Carapace length and wet weight growth of the juveniles were a¡ected by the presence or absence of other size groups, stocking density and animal size. All factors had statistically signi¢cant interactions, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 33 publications
1
12
1
Order By: Relevance
“…The A. astacus in communal stock reached higher weight than those in single treatment at the beginning of rearing. Ahvenharju et al (2005) reported that larger individuals of Pacifastacus leniusculus benefited from the presence of smaller co-species. Higher mortality or inter-specific cannibalism showed O. limosus in comparison to A. astacus at this period.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The A. astacus in communal stock reached higher weight than those in single treatment at the beginning of rearing. Ahvenharju et al (2005) reported that larger individuals of Pacifastacus leniusculus benefited from the presence of smaller co-species. Higher mortality or inter-specific cannibalism showed O. limosus in comparison to A. astacus at this period.…”
Section: Discussionmentioning
confidence: 97%
“…The smaller crayfish grew faster in the absence of large animals. However, smaller juveniles had more injuries than larger individuals even when reared separately (Ahvenharju et al, 2005). Chelae form a substatial proportion of crayfish total biomass.…”
Section: Discussionmentioning
confidence: 99%
“…2) is interesting, and implies that A. pallipes may in fact be influencing the population structure of the invading species. The moulting of juvenile P. leniusculus is synchronized, resulting in reduced intraspecific cannibalism (referenced in Ahvenharju et al 2005). However, interspecific predation by the native A. pallipes (Gil-Sánchez and AlbaTercedor 2006) as well as other predators such as fish (Söderbäck 1992) may underpin the observed reduction in juvenile P. leniusculus in mixed populations.…”
Section: Competitive Interactionsmentioning
confidence: 93%
“…Captive‐breeding for reintroduction is becoming a recognized conservation measure to try and halt population declines (Nightingale et al, ; Taugbøl & Peay, ). High survival rates can be achieved when raising young‐of‐the‐year A. pallipes ; however, even at low densities, there can be a large variation in size and health of crayfish juveniles within a single brood, even as early as 6‐months of age (Ahvenharju, Savolainen, Tulonen, & Ruohonen, ; J Nightingale pers. obs.…”
Section: Introductionmentioning
confidence: 99%